Hemostatic Ability of Thermosensitive Biologically Active Gelatin-Alginate Hydrogels Modified with Humic Acids and Impregnated with Aminocaproic Acid - Miroshnichenko, Denis; Lebedeva, Katerina; Lebedev, Vladimir; Cherkashina Аnna; Petrushenko, Sergey; Hrubnyk, Ihor; Yudina, Yulia; Bogoyavlenska, Olena; Klochko, Natalja; Lysenko, Liudmyla; Miroshnychenko, Mykhailo (Journal of Research Updates in Polymer Science, 2024)
The article studies the hemostatic ability of thermosensitive biopolymer hydrogels containing 14% by weight of gelatin and 6.4% by weight of sodium alginate, impregnated with a hemostatic agent aminocaproic acid 0.2 g/ml, with the addition of humic acids with antioxidant, antibacterial, fungicidal and anti-inflammatory properties. Modification of hydrogels with humic acids slightly increases viscosity, but maintains the gel-sol transition temperature close to the physiological temperature of about 37 °C, which allows them to melt on human skin or inside a wound, ensuring the delivery of aminocaproic acid. SEM images showed that the developed hydrogels have a layered internal morphology, which is improved due to better swelling of the hydrogels contained humic acids, which promotes the dissolution of aminocaproic acid inside the hydrogels and its subsequent rapid delivery to the bleeding site when applying a hydrogel dressing. It has been experimentally established that the concentration of humic acids in hydrogels of no more than 5 wt.% promotes blood clotting due to the entry of aminocaproic acid into it from the hydrogels. The aminocaproic acid delivered at physiological temperature from these hydrogels can shorten the blood clotting time to the lower limit of the normal clotting time range. The clotting time of the hydrogel with 5 wt.% humic acid is only 95 s, which confirms its particularly effective hemostatic ability.